2022
DOI: 10.3233/atde220186
|View full text |Cite
|
Sign up to set email alerts
|

Skills Matching for a Greener Industry 4.0 – A Literature Review

Abstract: Manufacturing industry has historically had a very high leverage on environmental impact. Therefore, it is urgent to identify how the industry and its employees can contribute to change towards a sustainable society. Industry leaders need to enable their employees to create sustainable solutions, using technologies rising in industry 4.0. However, nowadays there are also critical discussions about whether this trend has reached our workplace settings in a satisfactory way. Namely, there is a growing skill gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Their findings also showed that engineers are among the groups that are the most affected by both skills and educational mismatch and that most of the engineers, indeed, are not employed in engineering jobs. Braun et al (2022), on the other hand, pointed to a growing skills gap among workers in manufacturing industries. The findings Flores et al (2020) predicted a significant change in human capital in the future of Industry 4.0 and proposed a human-oriented perspective for companies within the new Industrial Revolution.…”
mentioning
confidence: 99%
“…Their findings also showed that engineers are among the groups that are the most affected by both skills and educational mismatch and that most of the engineers, indeed, are not employed in engineering jobs. Braun et al (2022), on the other hand, pointed to a growing skills gap among workers in manufacturing industries. The findings Flores et al (2020) predicted a significant change in human capital in the future of Industry 4.0 and proposed a human-oriented perspective for companies within the new Industrial Revolution.…”
mentioning
confidence: 99%